Jambore Literasi Sebagai Upaya Penguatan Baca Tulis bagi Siswa SLB B Yakut Purwokerto - Yulianti, Uki Hares; Yulianita, Nadia Gitya; Resticka, Gita Angria (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
There is a problem in the SLB B Yakut education report, namely that the reading skills of SLB students are still lacking. This is due to several factors, such as the implementation of the school literacy movement for deaf children at SLB B Yakut Purwokerto has not been running well, a lack of non-academic books, and teachers have not maximized learning innovations. Therefore, this community service activity aims to improve the literacy skills of SLB students, particularly those who are deaf and mute. The methods used for this community service activity include Forum Group Discussions (FGD), socialization, training, and mentoring for both teachers and SLB students. This literacy improvement activity consists of several stages, beginning with a Forum Group Discussion (FGD) between the community service team and the school, socialization of the School Literacy Movement (GLS) for SLB teachers to reactivate GLS activities, and literacy training packaged into several activities. The series of literacy training activities includes writing literacy training conducted using out-of-classroom learning methods.Furthermore, the application of technology through educational games for learning English and training in Canva for poster creation is also part of a series of literacy training activities. The service team also provides ongoing support for these activities, enabling the successful implementation of a literacy jamboree that produces various student works from the Special Education School (SLB), including poems, prose, and posters. The reading skills of SLB students have improved significantly due to the active daily participation in GLS activities, and their writing skills have also improved, as evidenced by the students' works in the form of prose, poems, and posters.